A Case of Fever and Erythema Nodosum-Like Lesions Leading to a New Diagnosis of Gamma-Delta T-Cell Lymphoma Complicated by Hemophagocytic Lymphohistiocytosis - William S. Murphy; Jennifer E. Yeh; Rosalynn M. Nazarian; Aliyah R. Sohani; Joseph Kvedar; Daniela Kroshinsky (MDPI AG, 2020)
A 69-year-old Vietnamese female presented with fever and new-onset tender subcutaneous nodules on her trunk and lower extremities initially thought to be clinically consistent with erythema nodosum. A biopsy showed an atypical, predominantly lobular lymphocytic panniculitis with admixed neutrophils, karyorrhectic debris, and histiocytes with subcutaneous fat necrosis. Immunohistochemistry was consistent with gamma-delta T-cell lymphoma. The patient was initiated on a chemotherapy regimen of cyclophosphamide, doxorubicin, vincristine, etoposide, and prednisone (CHOEP) with partial remission, and is currently undergoing evaluation for bone marrow transplant. This case highlights the ability of cutaneous gamma-delta T-cell lymphoma to mimic more common cutaneous conditions such as erythema nodosum, and stresses the importance of a broad differential for new presentation of tender subcutaneous nodules with concomitant systemic symptoms.